2019
DOI: 10.1111/vde.12795
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of N‐acetylcysteine in combination with antimicrobials on common canine otitis externa bacterial isolates

Abstract: Background -Approved treatments for canine otitis externa are limited in variety and may contain ototoxic ingredients. With bacterial resistance an ongoing concern, it would be ideal if non-ototoxic agents combined with antibiotics resulted in a synergistic effect, requiring lower antibiotic concentrations to treat infections. Evidence of synergism and antagonism between N-acetylcysteine (NAC) and various antibiotic classes has been reported; the present research group was interested in examining these interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Most combinations of NAC with antibiotics displayed different interactions against P. aeruginosa except for four isolates. The rate of synergistic interactions was similar to a previous study, but the rate of antagonistic interactions was lower [20]. Almost all combinations against P. aeruginosa were similar.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Most combinations of NAC with antibiotics displayed different interactions against P. aeruginosa except for four isolates. The rate of synergistic interactions was similar to a previous study, but the rate of antagonistic interactions was lower [20]. Almost all combinations against P. aeruginosa were similar.…”
Section: Discussionsupporting
confidence: 86%
“…The antimicrobial and antibiofilm activities of NAC in combination with antimicrobials against P. aeruginosa have been studied [16,17,20]. The present study assessed the in vitro efficacy of NAC combined with enrofloxacin, polymyxin B, and gentamicin against P. aeruginosa isolated from dogs with OE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It therefore possible that NAC and similar anti-biofilm compounds may aid treatment of biofilm-associated infections in animals 2 . A commercially available trisEDTA-NAC solution may facilitate removal and treatment of biofilms in ear canals, although time should be left between this and topical antibiotics as an in vitro study found most interactions between NAC and enrofloxacin or gentamicin were indifferent to antagonistic 49 . Other compounds with potential anti-biofilm and antimicrobial activity include chlorhexidine, polihexanide, hypochlorous acid 44,50 and trisEDTA 2 .…”
Section: Biofilmsmentioning
confidence: 99%
“…N-acetylcysteine (NAC) is another candidate being explored as an adjuvant for use in canine OE. Similarly to Tris-EDTA, it has been shown to inhibit the growth of P. aeruginosa, including in canine otitis clinical isolates [97,137,138]. Synergistic interactions between NAC and enrofloxacin or gentamicin have been observed for one P. aeruginosa isolate, but were indifferent or antagonistic at the concentrations tested in vitro for most isolates [137].…”
Section: Potential Alternative Treatmentsmentioning
confidence: 99%